THE USE OF MONOLOGUE PERFORMANCE OF SOUTH SULAWESI FOLKLORE TO IMPROVE STUDENTS’ SPEAKING ABILITY AT THE ELEVENTH GRADE STUDENTS OF MA ASSALAM TIMBUSENG - Malida Ibrahim; Ratna Dewi; Firman (FKIP Unismuh Makassar, 2021)
This research aimed to improve students’ speaking ability at the Eleventh Grade of MA Assalam Timbuseng using Monologue Performance of South Sulawesi Folklore. The researcher used Classroom Action Research where the data gained from the speaking test. The subjects of the research were 27 students of the Eleventh Grade of MA Assalam Timbuseng in the Academic Year 2020/2021. The research findings showed that the students’ speaking ability before and after using monologue performance was significantly different. The students’ D-test mean score in terms of fluency was 66.63 while in final test cycle 1 was 71.78 improvement, however it still did not get the standardization score of English subjects (75). Then, the mean score in terms of fluency in final test cycle 1 was 79.89 which mean there was 11.29% improvement from cycle 1 through cycle 2. Furthermore, students’ score frequency in terms of fluency in cycle 1, it can be seen that there are 7 (26%) students got good, 19 (70%) students got fair and 1 (4%) student got poor. Then, the students showed the improvement in cycle 2 which is 9 (33%) students got very good, 17 (63%) students got good and 1 (4%) student got fair. It means that there was a significant improvement of students’ speaking ability after using monologue performance of south Sulawesi folklore. Based on the findings, it can be concluded that digital storytelling was effective to improve students’ speaking ability at the Eleventh Grade of MA Assalam Timbuseng in the Academic Year 2020/2021.